Government transparency and expenditure in the rent-seeking industry: The case of Japan for 1998–2004 - Eiji Yamamura; Haruo Kondoh (Economics and Econometrics Research Institute (EERI), 2012)
Since the end of the 1990s, local governments in Japan have enacted Information Disclosure Ordinances, which require the disclosure of official government information. This paper uses Japanese prefecture-level data for the period 1998–2004 to examine how this enactment affected the rate of government construction expenditure. The Dynamic Panel model is used to control for unobserved prefecture-specific effects and endogenous bias. The major finding is that disclosure of government information reduces the rate of government construction expenditure. This implies that information disclosure reduces losses from rent-seeking activity, which is consistent with public choice theory.
Keywords: D73; D78; H79; 330; Information disclosure; Special interest group; Construction expenditure; Rent seeking